Utilisation of oil palm empty fruit bunch ash as potential natural coagulant for palm oil mill effluent treatment / Nur Syahira Hisham and Zadariana Jamil - Hisham, Nur Syahira; Jamil, Zadariana (Universiti Teknologi MARA Cawangan Pahang, 2020)
The palm oil mill industry generates massive wastes in solid and liquid forms such as Empty fruit bunches (EFB) and palm oil mill effluent (POME). These two wastes are high in fibre and organic content that may affect the environment and health without proper management. Thus, the recovery of these valuable resources from wastes is vital in order to reduce pollutions generated from palm oil production. The empty fruit bunch ash (EFBA) was investigated to determine its potential as a natural coagulant for COD and TSS removal in palm oil mill effluent (POME). The effectiveness of EFBA was determined by varying the parameters such as coagulant dosage (0 – 22 g/l) and initial pH of POME (3 – 4). The maximum removal of COD and TSS were about 39.96% and 77.09% respectively at initial POME pH of 4 and EFBA dosage of 6 g/l, suggesting EFBA as a new alternative coagulant for treating palm oil mill effluent.